Dent de loup et cœur de cerf : observations sur la place de l’animal dans l’idéologie de la guerre et du sacrifice à Teotihuacan - Nicolas Latsanopoulos (Journal de la Société des Américanistes)
Wolf tooth and deer heart : observations about animal importance in warfare and sacrificial ideology at Teotihuacan. This paper offers a study about the symbolic importance of two animal families in the Teotihuacan martial and sacrificial ideology. The scarce data about cervidae evoke essentially a game-victim, an impression strengthened by the recurrent association between deer and canid which, as much as in faunal remains as in pictures, establishes the conventional prey-predator pair. The first big canid pictorial manifestation dates back to the third century A.D., while the canid-warrior image will generalize in later times. The description of faunal remains of the Moon pyramid attests to the unsuspected importance of the grey wolf in the system of beliefs from Classic Central Highlands and seem to prefigure the Postclassic Nahua « eagle, jaguar, wolf » triad. The study of canidae maxillar collars of the Feathered Serpent pyramid also testifies to the original hybridation practices among domestic, wild and hybrid canidae.